Pathogenic mutations in two families with congenital cataract identified with whole-exome sequencing - Kondo, Yukiko (Molecular Vision, 2013)
PURPOSE: Congenital cataract is one of the most frequent causes of visual impairment and childhood blindness. Approximately one quarter to one third of congenital cataract cases may have a genetic cause. However, phenotypic variability and genetic heterogeneity hamper correct genetic diagnosis. In this study, we used whole-exome sequencing (WES) to identify pathogenic mutations in two Korean families with congenital cataract. METHODS: Two affected members from each family were pooled and processed for WES. The detected variants were confirmed with direct sequencing. RESULTS: WES readily identified a CRYAA mutation in family A and a CRYGC mutation in family B. The c.61C>T (p.R21W) mutation in CRYAA has been previously reported in a family with congenital cataract and microcornea. The novel mutation, c.124delT, in CRYGC may lead to a premature stop codon (p.C42Afs*60). CONCLUSIONS: This study clearly shows the efficacy of WES for rapid genetic diagnosis of congenital cataract with an unknown cause. WES will be the first choice for clinical services in the near future, providing useful information for genetic counseling and family planning.